2014
DOI: 10.1149/2.0871501jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Majority Carrier Transport in WO3Water Oxidation Photoanode via Electrochemical Doping

Abstract: Here we report an electrochemical reduction-induced photocurrent enhancement up to an order of magnitude for monoclinic tungsten trioxide (WO 3 ) particulate photoanodes. Electrochemical impedance and photoelectrochemical measurements suggest that the improved performance is attributed to the increase in majority carrier concentration (from 1.5 × 10 18 to 2.5 × 10 21 cm −3 ). This results in higher conductivity and improved electron transport. Minority carrier extraction can be increased by reducing the WO 3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 58 publications
4
43
0
Order By: Relevance
“…Our observations are qualitatively in line with a recent report by Osterloh and co‐workers . By using electrochemical impedance spectroscopy, these authors showed that the photocurrent enhancement by up to an order of magnitude upon moderate electrochemical doping of monoclinic WO 3 electrodes was accompanied by an up to three orders of magnitude increase in majority carrier concentration and by an increase in the conductivity of the porous film.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our observations are qualitatively in line with a recent report by Osterloh and co‐workers . By using electrochemical impedance spectroscopy, these authors showed that the photocurrent enhancement by up to an order of magnitude upon moderate electrochemical doping of monoclinic WO 3 electrodes was accompanied by an up to three orders of magnitude increase in majority carrier concentration and by an increase in the conductivity of the porous film.…”
Section: Resultssupporting
confidence: 93%
“…Based on our results and in line with a previous report, we attribute the photocurrent increase observed for WO 3 (450) electrodes after moderate doping to the accumulation of electrons in the semiconductor particles (Figure ). Adsorption and insertion of protons from the electrolyte compensate the accumulated negative charge, thus forming (e − /H + ) centers in the oxide.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in surface states is also known to pin the Fermi level of the photocatalyst, and results in an anodic shift in the onset potential. 29 This offsets the Figure 9 Energy band alignment diagrams for Co3O4/WO3, Conduction and valence band edge positions of Co3O4 and WO3 material are obtained from literature. 21,22 cathodic shift normally observed with the introduction of a cocatalyst, and may account for why only a marginal shift in onset potential has been observed ( Figure 6).…”
Section: Resultsmentioning
confidence: 94%